Strategy in Promotion E-Tourism Base: Study on Bantaeng Regional Government - Hermawati Amiruddin (Newinera Publisher, 2020)
This study aims to determine the strategy of local government in promotion based on E-Tourism in Bantaeng Regency and also to find out what factors influence the local government in the formulation of E-Tourism-based promotion strategy in Bantaeng Regency. This type of research is descriptive qualitative with the type of phenomenological research. Data is collected from interviews, then analyzed based on indicators of Human Resources, Facilities and Infrastructure, and Funding. Data collection techniques carried out by observation (observation), interviews (interviews), and documentation. The results of this study indicate that the Bantaeng Regency government's strategy in implementing E-Tourism is maximized by creating a Team filled with human resources who have a special capacity or ability in IT mastery. Specifically, for the concept of E-Tourism, limiting physical funding, but for technical expertise, technical financing such as photographers and graphic design experts is required. Supporting factors for E-Tourism based promotion in Bantaeng Regency are the apparatus commitment to promoting Bantaeng tourism and collaboration with various parties.